Combined healthy lifestyle factors and risk of all-cause and cardiovascular first hospitalization. (13th November 2019) - Bonaccio, M; Di Castelnuovo, A; Costanzo, S; Persichillo, M; De Curtis, A; Cerletti, C; Donati, M D; de Gaetano, G; Iacoviello, L
Abstract: Background: We aimed to explore the association of combined healthy lifestyles with risk of first hospitalization for all-cause, cardiovascular disease (CVD), ischemic heart disease (IHD) and stroke in a southern Italian population-based cohort. We also investigated several biological mechanisms possibly on the pathway between lifestyles and health outcomes. Methods: Longitudinal analysis on 23, 161 men and women (aged≥35 y) recruited in the Moli-sani Study (2005-2010). We defined 4 healthy lifestyle factors as abstention from smoking; high adherence to Mediterranean diet; physical activity; absence of abdominal obesity. First hospital admissions for any and CVD-related causes were recorded by direct linkage with hospital discharge form registry. Hazard ratios (HR) with 95% confidence interval (95%CI) were calculated by multivariable Cox-regression. Results: Over a median follow up of 7.2 y, we ascertained a total of 9, 482 hospitalizations, 3, 556 CVD, 939 IHD and 589 stroke-related hospital admissions. Adherence to all four healthy lifestyles, compared with none or 1, was associated with lower risk of hospitalization for any cause (HR = 0.82; 0.74-0.90), CVD (HR = 0.81;0.69-0.95) and IHD (HR = 0.63; 0.44-0.90) and, to a less extent, with stroke hospitalizations. Inflammatory biomarkers (e.g. C-reactive protein) were likely to partly explain the association between lifestyles and all-cause (14%) or CVD (15%) hospitalizations, while inflammation played a leading role towards risk of IHD (30%) and stroke-related hospital admissions (21%). Conclusions: The impact of combined 4 healthy lifestyles on first hospitalization risk was considerable. Inflammatory biomarkers explained a large proportion of this association. Key messages: Improvements to lifestyle reduce the risk of hospitalizations in a general adult population. Achieving a greater number of healthy behaviours has the potential to reduce the burden of hospitalizations and the associated healthcare costs.